LEGALITAS RIWAYAT ASBĀB AL-NUZŪL Telaah historis konteks turunya ayat al-Quran - Abd Kholid (Jurnal Theologia, 2013)
Abstract: Asbāb al-Nuzūl (occasions of revelation) is event becoming background send down the verse of the Quran. Scope solution of Asbāb al-Nuzūl only relating to event degrading of the verse of the Quran especially in event relation and word expression, that include texts or materials. This science is very importance in order to interpret the verses of the Quran. This is not mean that it is to generalize interpretation entire verses of the Quran with Asbāb al-Nuzūl, because there is not all verses of the Quran send down with Asbāb al-Nuzūl. But, for the verses of the Quran have Asbāb al-Nuzūl, that its interpretation is more authentic. Abstrak: Asbāb al-Nuzūl adalah peristiwa yang menjadi latar belakang turunnya ayat al-Quran. Ruang lingkup pembahasan Asbāb al-Nuzūl hanya berkaitan dengan peristiwa diturunkannya ayat al-Quran terutama dalam hubungan peristiwa dan ungkapan kata, baik teks ayat, maupun redaksi ayat. Ilmu ini sangat penting dalam rangka menafsirkan ayat-ayat al-Quran. Hal ini bukan berarti menggeneralisasi keharusan menafsirkan seluruh ayat al-Quran dengan Asbāb al-Nuzūl, karena tidak semua ayat al-Quran turun disertai dengan Asbāb al-Nuzūl. Akan tetapi bagi ayat-ayat al-Quran yang memiliki Asbāb al-Nuzūl, maka penafsirannya akan lebih otentik. Kata-kata Kunci: asbāb al-nuzūl, ‘ulūm al-Qur’ān, ilmu Ma‘ānī dan Ilmu Bayān, Nabi Muḥammad, dan sahabat.